Reforming character curriculum through Qur’anic insights: The pedagogical relevance of Luqman’s wisdom (Q.S. 31:13–19) - Alhamuddin, Alhamuddin; Murniati, Andi; Arifin, Abdul Gafur; Akhirudin, Muhamad Towil (Sekolah TInggi Ilmu Tarbiah Al Bukhary Labuhanbatu, 2025)
This study aimed to explore the pedagogical relevance of Luqman’s counsel (Q.S. 31:13–19) as a foundation for character curriculum reform in schools. The purpose was to address the gap between ideal Islamic moral teachings and the realities of character education practices. A qualitative approach with textual and document-based methods was used. The research drew from classical and contemporary tafsir, educational literature, and curriculum development theories related to moral and spiritual formation. The results showed that Luqman’s counsel offered a comprehensive framework that integrated intellectual understanding, emotional growth, behavioral guidance, and spiritual values. Five main themes emerged: the unity of faith and ethics (tawḥīd), the importanceof gratitude and humility, respect for parents, moral strength through patience and self-awareness, and alignment with modern holistic curriculum models. The study concluded that the values embedded in Luqman’s advice supported the development of a culturally authentic and morally grounded curriculum. These principles helped enrich character education by providing spiritual depth and practical relevance for students’ lives. The study recommended that educators and curriculum designers incorporate Luqman’s values into learning programs to enhance moral development and ensure educational content remains meaningful within Muslim contexts.